RECIPROCITY IN PSYCHOLOGICAL CONTRACT AND CHANGE-ORIENTED ORGANISATIONAL CITIZENSHIP BEHAVIOUR OF HOTEL INDUSTRY IN NIGERIA - Genesis Odiyah Mulade; Dr. Omoankhanlen J. Akhigbe (EPRA International Journal of Research and Development (IJRD), 2022)
The goal of this research is to discover the nature of the link between reciprocity in psychological contract and change-oriented organisational citizenship behaviour. The research issue is that, since the fall of the Naira, the emergence of COVID-19, the limits, and income loss, the responsibility of hotel success has been placed on the shoulders of the leader. As a result, the innovative atmosphere is obsolete, and managers are implementing drastic initiatives that are not in line with employee expectations. To acquire a picture of the hotel sector, a cross-sectional survey was used, coupled with other mixed research approaches for a broader view. The figures were gathered through an online poll of 243 hotel employees working in premium hotels in South-South Nigeria. The research findings were obtained through the use of structural equation modelling.